Pedagogical Competence Of Teachers In Managing The Learning Process - Huda, Wahyul (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2022)
The purpose of this research is to interpret teachers' pedagogical competencies in instructional management. This study uses a qualitative descriptive method in the form of a literature review (library research), which primarily utilizes books and other literature as its main objects. The results of this research consist of sub-competencies of pedagogy that teachers should possess in instructional management. Pedagogical competence refers to a teacher's ability in managing students' learning processes, which includes, at the very least, understanding educational insights or foundations, understanding students, curriculum/syllabus development, instructional design, educative and dialogic teaching implementation, utilization of instructional technology, evaluation of learning outcomes, and student development to actualize their various potentials.